Kirigami nanofluidics. (31st January 2018) - Gao, J.; Koltonow, A. R.; Raidongia, K.; Beckerman, B.; Boon, N.; Luijten, E.; Olvera de la Cruz, M.; Huang, J.
Abstract : Kirigami nanofluidics is demonstrated here, where ionic transport through 2D laminar films can be manipulated by tailor-cutting the film shape. Abstract : Exfoliated thin sheets of layered materials can readily reassemble to form a macroscopic lamellar film containing a massive array of parallel two-dimensional (2D) nanochannels. These 2D nanofluidic channels exhibit enhanced unipolar ionic conductivity with the counterions as the majority charge carriers, thus conceptually become an ionic analogue of extrinsically doped semiconductor wafers. Here we demonstrate "kirigami nanofluidics", where ionic transport can be manipulated by tailor-cutting the shape of the film. Shapes with an asymmetric source and drain exhibit rectifying ionic currents, which is attributed to the asymmetric concentration polarization zones developed in the two reservoirs. Therefore, the rectification ratio can be continuously tuned simply by adjusting the relative edge sizes of the shape, or even programmed by selecting the number of source and drain branches in multi-armed shapes. Kirigami-made ionic rectifiers and resistors can be conveniently connected together to demonstrate simple AND and OR logic functions. These results demonstrate nanoscale ionic transport can be manipulated by patterning materials at the macroscopic length scale.